2020
DOI: 10.1001/jamahealthforum.2020.1094
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Health Insurance Profits and the COVID-19 Crisis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has placed unprecedented financial stress on most of the US health care system, including physician practices, emergency medical service systems, and hospitals. But there is one notable exception: health insurance companies. Sharp declines in elective care during the pandemic have reduced health care expenditures and contributed to earnings that are twice as large as those earned last year. For example, the UnitedHealth Group's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Finally, as we continue in our fight against the Covid‐19 pandemic, we call upon the payors to invest some of their record gains 3 to improve their own denial systems—as a measure to alleviate these unnecessary burdens on healthcare workers and healthcare systems already under immense stress.…”
Section: What Can Be Done?mentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, as we continue in our fight against the Covid‐19 pandemic, we call upon the payors to invest some of their record gains 3 to improve their own denial systems—as a measure to alleviate these unnecessary burdens on healthcare workers and healthcare systems already under immense stress.…”
Section: What Can Be Done?mentioning
confidence: 99%
“…Further, hospitals and health systems should attempt to proactively define rules of engagement during the denials process in their contracts with payorsincluding limiting the number of denials, timeliness and ease of scheduling discussions and rules for professional behavior during discussions. 6 Finally, as we continue in our fight against the Covid-19 pandemic, we call upon the payors to invest some of their record gains 3 to improve their own denial systems-as a measure to alleviate these unnecessary burdens on healthcare workers and healthcare systems already under immense stress.…”
Section: Meaningful Transparencymentioning
confidence: 99%
See 2 more Smart Citations
“…Calls for payers to take action were amplifi ed after fi nancial records indicated that prominent insurers registered medical loss ratios (MLRs) below 80% and also realized substantial profi ts during the Published May 17, 2021 second quarter of 2020 due to pandemic-induced declines in utilization [73,74,75]. While payers who meet government-determined criteria for MLRs will be required to provide consumers with rebates, the broader increase in gross margins per member per month (e.g., 35% increase in Medicare Advantage) spurred calls for health plans to increase their contributions to health system and public health needs [27,76].…”
Section: Securing Buy-in For Valuementioning
confidence: 99%